1、 1. A 2 A B C B C 3 4 A 2 1 6 A B C 2 3 4 A 1 B A = 1 B = 1 1+1 + 1+1 3 + C +1 4 = 2 1 6 12 + 8 12 2 12 3 3 12 + + = C 26 12 12 + 8 + 3C+ 3 = 26 C = 1 C = 1 A = 1 B = 2 1+1 + 2 +1 3 + C +1 4 = 2 1 6 1+1+ C +1 4 = 2 1 62 1+1+ C +1 4 = 2 1 6 C +1 = 1 6 C 4 2. 8 3 1 11 4 5 35 8 45 120 9 21 1 45 1 1 45
2、45 8 + 3 8 + 1 45 + 11 120 + 4 9 + 5 21 3 = 7 15 351 45 = 20 45 = 4 9 1 4 45 9 1+ 1 4 21 +19 1 + 1 4 = 40 4 = 32 32 1 = 8 32 -19 = 13 8 8 5 4 13 13 73 2 136 9 3 5 = 3 3 5 3 = 9 15 = 1+8 7 + 8 7. 5 15 1 28 56 1 20 n m n m 2 5 8 = a n m 15 = b 56 n m 1 1 20 = c n m 28 = a n m 56 = b n m 20 = c 5 15 21
3、 n m = 105 4 = 26 1 4 26 1 4 1 + 1 3 + 1 2 = 1 42 7 42 42 1 = 1 42 1 20 5 2 1 = 2 12 1 = 2 10 2 6 5 11 3 1 = 3 18 1 = 3 15 3 6 5 17 5 1 = 5 30 1 = 5 25 5 6 5 29 7 1 = 7 42 1 = 7 35 7 7 6 5 37 41 11 11 13 13 17 17 19 59 61 71 73 89 97 97 13 2 3 5 7 11 17 29 37 7 14 111 59 11 61 13 13 13 17 17 19 67 7
4、1 73 89 97 97 1 1 + 1 17 20 19 2 1 + 1 29 30 24 3 1 + 1 37 40 31 4 1 + 1 47 50 41 1 1 + 1 17 20 = 2 + 3 + 1 19 = 2 + 9 + 3 57 19 17 51 2 1 + 1 29 30 = 2 + 1 + 1 29 = 2 + 9 + 3 87 24 4 36 3 1 + 1 37 40 = 2 + 9 + 3 37 4 1 + 1 47 50 = 2 + 9 + 3 47 31 31 41 41 1 + 1 37 40 31 1 + 1 37 40 31 11. A B A + B 3 = 17 33 A + B 11 A + B 3 = 17 33 11 3 11 A 11 + B 3 3A + 11B 33 = 3A +11B 33 = 17 33 A B 33 12. 1 + 1 4 +